Clinical presentation and prognostic analysis of Chinese patients with systemic light chain amyloidosis with liver involvement. (November 2019) - Zhang, Le-le; Shen, Kai-ni; Zhang, Cong-li; Qiu, Yu; Miao, Hui-lei; Feng, Jun; Cao, Xin-xin; Zhang, Lu; Zhou, Dao-bin; Li, Jian
Highlights: More than 95% of patients with hepatic systemic AL amyloidosis showed the involvement of other organs. Elevation of total bilirubin indicated worse PFS and OS. The early death rate was 48.5% in the patients with elevated total bilirubin. Abstract: To summarize the clinical characteristics and prognostic factors of Chinese patients with systemic light chain amyloidosis with liver involvement. We retrospectively analyzed the clinical features and natural history data of 102 patients diagnosed with systemic light chain amyloidosis with liver involvement at Peking Union Medical College Hospital between March 2007 and May 2018. More than 95% of patients showed the involvement of other organs. Kidney and heart were the most frequently involved organs, accounting for 71.6% and 68.6% of cases, respectively. Hepatomegaly was the most frequently observed physical sign, accounting for 67.6% of cases. Elevated levels of alkaline phosphatase (ALP) and gamma-glutamyl transferase (GGT) were frequently observed, accounting for 85.3% and 88.2% of cases, respectively. A significantly better prognosis was observed in patients with normal total bilirubin levels, as compared with those with elevated levels of total bilirubin. Patients in the normal total bilirubin group showed a significantly better progression-free survival (PFS) (38 months) as compared the elevated total bilirubin group (4 months; P < 0.001). The median overall survival (OS) in the normal total bilirubin group was not reached compared with the elevated total bilirubin group (4 months, P < 0.001). Notably, the early death rate was significantly lower in the normal total bilirubin group as compared to the elevated total bilirubin group (14.5% vs 48.5%, P < 0.001). In conclusion, the elevation of total bilirubin indicated an early death and worse PFS and OS. Early diagnosis is therefore essential, and requires appropriate treatment and intensive care.